SOME ACTUAL PROBLEMS OF THE INTERNATIONAL LEGAL REGULATION OF THE PROVISION OF INFORMATION SECURITY - Ефендієв, Октай; Алієв, Етібар (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article: to consider the main problems and features of the regulation of international information security in the context of globalization of interstate relations. Research methods: generally accepted methods of scientific knowledge were used, such as: analytical, comparative legal, semantic-cognitive, systemic, statistical and others. Results: the system of international information security, according to the authors of the article, should be a combination of international and national institutions designed to regulate the activities of various subjects of the global information space. Discussion: of individual issues of forming acceptable for all countries fair international information legal relations, which are important both for Azerbaijan and for the establishment of a new information world order. Ensuring information security in the modern world is becoming a global problem affecting the fundamental interests of both individuals, society, and each individual state. It is generally recognized that the quintessence of this problem is mainly the constantly growing threats to both the security of countries and the individual, society precisely from the information sphere, developing at a faster pace in comparison with all other vital areas of social life. It is characteristic that in the present era, these methods and technologies for ensuring information security lag behind the pace of development of the information sphere. Another feature is that information security is one of the components of global international security, the goal of which, ultimately, is to solve the problems associated with the development and implementation, for example, of various legal means to prevent wars and armed conflicts, normal interstate relations. And therefore, in a broad sense, it is obvious that all the normative material of modern international law, ultimately, provides for the solution of these most important problems.